ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI KOMBINASI DEEP BREATHING DAN LIGHT MASSAGE TERHADAP NYERI DAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RSPAD GATOT SOEBROTO - Dini Sholihatunnisa (2023)
Hypertension is a condition where there is an increase in blood pressure within normal limits that occurs persistently or continuously with a systolic pressure value of more than 140 mmHg and a diastolic pressure of more than 90 mmHg. Signs and symptoms experienced by patients with hypertension include headache which sometimes feels nauseous and vomiting due to increased intracranial blood pressure, blurred vision due to damage to the retina, balance disorders, frequent urination at night due to increased blood flow in the kidney. The treatment that can be done can use pharmacological therapy by taking drugs or non-pharmacological such as doing progressive muscle relaxation, deep breathing relaxation and doing reflexology. The intervention that the writer will do in this nursing care is deep breathing therapy and light massage, namely light touch therapy with soft tissue manipulation in the body by doing several massage movements, the movements that the writer is doing here are effleurage and friction. The purpose of this study was to determine whether there was a change in blood pressure in hypertensive patients before and after being given deep breathing and light massage therapy in managed and resume patients.